Mortality and morbidity among traditionally circumcised Xhosa boys in the Eastern Cape Province, South Africa - S.M. Mogotlane; J.T. Ntlangulela; B.G.A. Ogunbanjo (AOSIS, 2004)
Male circumcision is one of the oldest traditions observed by many societies. The ritual is performed at specific periods in life with the main purpose of integrating the male child into the society according to cultural norms. Recently, especially in the Eastern Cape, many initiates have died or have had to face life with mutilated genitals following this ritual.